Case Study: Implementation of Simple Inhalation Therapy Using Eucalyptus Oil Aromatherapy for Ineffective Airway Clearance in a Child with Acute Respiratory Infection - Kurniawan, Ade; Firmansyah, Andan; Supriadi, Dedi (Genius Journal, 2025)
Introduction: Upper Respiratory Tract Infections (URTIs) are acute infections that affect the respiratory tract from the nose to the alveoli, including related organs such as the sinuses, middle ear cavity, and pleura. According to the World Health Organization (WHO) report in 2024, URTIs account for 6% of the global disease burden, resulting in approximately 6.6 million child deaths annually, with 95% of these fatalities occurring in low-income countries. The incidence of pneumonia in West Java was reported at 32.2% in 2020, increasing to 44.9% in 2022. Data from Ciamis Regency indicates that URTIs represent the disease with the highest prevalence. In 2019, the highest number of cases of pneumonia among toddlers was recorded in Cipaku (350 cases), Rancah (324 cases), and Banjarsari. Objective: The objective of this case study is to examine children experiencing Upper Respiratory Tract Infections (URTIs) with ineffective airway clearance. Method: The research design employed is a descriptive case study with a nursing care approach for children with Upper Respiratory Tract Infections (URTI). Result: The results of the case study during the assessment phase revealed that the client was experiencing productive cough. Following the assessment, a diagnosis of Upper Respiratory Tract Infection (URTI) was established, specifically identifying ineffective airway clearance (D. 0001) related to retained secretions. The intervention plan focused on administering simple inhalation therapy using eucalyptus oil aromatherapy. This inhalation was conducted for 10-15 minutes in two sessions per day, in the morning and evening, over a consecutive three-day period. The evaluation indicates an improvement in airway patency in the patient, An.M, diagnosed with URTI. Conclusion: In conclusion, the implementation of simple inhalation therapy using eucalyptus oil has proven to be effective in demonstrating improvements in airway clearance in the patient, An.M.